2009
DOI: 10.1215/15228517-2008-113
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analyses of gene copy number and mRNA expression in glioblastoma multiforme tumors and xenografts

Abstract: Development of model systems that recapitulate the molecular heterogeneity observed among glioblastoma multiforme (GBM) tumors will expedite the testing of targeted molecular therapeutic strategies for GBM treatment. In this study, we profiled DNA copy number and mRNA expression in 21 independent GBM tumor lines maintained as subcutaneous xenografts (GBMX), and compared GBMX molecular signatures to those observed in GBM clinical specimens derived from the Cancer Genome Atlas (TCGA). The predominant copy number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
99
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 55 publications
(66 reference statements)
9
99
0
4
Order By: Relevance
“…Amplification of this region, although infrequent, has been implicated in various human cancers (24)(25)(26)(27)(28)(29). Our array CGH (comparative genomic hybridization) analysis revealed amplification of YAP1 in 1 of 9 gastric cancer cell lines only (NCI-N87; Supplementary Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Amplification of this region, although infrequent, has been implicated in various human cancers (24)(25)(26)(27)(28)(29). Our array CGH (comparative genomic hybridization) analysis revealed amplification of YAP1 in 1 of 9 gastric cancer cell lines only (NCI-N87; Supplementary Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Tumor cells were cultured as tumorspheres, using neural stem cell conditions including non-adherent growth and minimal essential media, to promote retention of tumor generating cells (40,41). The four human lines were selected based on their diversity of molecular and transcriptional properties, including EGFR amplification and EGFRvIII expression in GBM6, PDGFRA amplification in GBM5, and CDKN2C/p18(INK4c) homozygous deletion in GBM43 (35,36,42). Nanostring analysis of tumorsphere mRNA confirmed differences between the lines, including EGFR and EGFRvIII expression in GBM6, low expression of NF1 in GBM43, and robust expression of PDGFRA in all four lines (Supplemental Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…GBM43, GBM6, and GBM5 are tumorsphere cultures of patient-derived xenografts (PDX). PDX were established as previously described (34,35) and have been genetically and transcriptionally profiled (1,35,36). GBM1 (SF9487) is a newly generated primary patient-derived tumorsphere culture from UCSF and when injected into the striatum of nude mice generates highly invasive GBM (Supplemental Figure 1, Supplemental Table 1, and Supplemental Material and Methods).…”
Section: Methodsmentioning
confidence: 99%
“…We have reported that there is a significant increase in MMP-1 mRNA levels in tumor samples from patients with GBM relative to normal brain [13]. MMP-1, which is not typically expressed in normal brain, has been shown to be elevated in gliomas [22] and correlates with tumor grade and survival time [12].…”
Section: Introductionmentioning
confidence: 97%